APLICATION NUMERICAL MODEL TO STUDY ON MAXIMUM TURBIDITY ZONES IN BACH DANG ESTUARY - Vinh, Vu Duy; Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2012)
Recent researches on dynamics of land- sea interaction in estuaries have discovered a zone with very high turbidity or maximum turbidity zone (MTZ). This zone is rich in the nutrients concerning abundance of marine biological resources, and high in potential of pollutant accumulation. The studied using Delf-3D Model in this paper has discovered MTZ in Bach Dang Estuary. Its scale and location are changed by river discharge in seasons, and tidal oscillation. The furthest location of MTZ in this estuary is about 15km from shoreline during the ebb tide in rainy season. In the dry season, it is smaller in scale and moves closed to the coast.